Improvement in chemical properties of degraded peatlands, physiological characteristics, and soybean yield using dolomite - Asie, Erina Riak; Rumbang, Nyahu; Chotimah, Hastin E.N.C.; Darung, Untung; Saputra, Marcelino A.; Yurisinthae, Erlinda; Nurmayulis, Nurmayulis (Brawijaya University, 2025)
Degraded peatlands are natural resources that must be managed properly. The unique characteristics of degraded peatlands, such as high acidity and low availability of macro and micronutrients, are the main challenges in soybean cultivation. The pot experiment was conducted using a completely randomized design consisting of four dolomite dosage levels, namely 0, 3, 6, and 9 t/ha, with five replications. The research objective was to assess the effect of dolomite application on the chemical properties of degraded peatland, physiological characteristics, and soybean yield. The results showed that dolomite application significantly improved the chemical properties of degraded peatlands and increased the physiological characteristics and yield of soybeans. Dolomite at a dose of 6 or 9 t/ha achieved the highest pH, exchangeable Ca, and exchangeable Mg after incubation and after harvest. The highest total chlorophyll and average net assimilation rate were obtained at 9 t/ha dolomite application of 3.95 mg/g and 0.048 g/cm2/day, respectively. The relationship between dolomite and the total chlorophyll content of soybean plants was very strong (r = 0.94) with the equation y = 0.35 + 0.37x. The highest soybean seed weight was observed when dolomite was applied at a dose of 9 t/ha, resulting in 9.72 g/plant, an increase of 219.70% compared to the control. These findings suggest that optimal dolomite application can enhance the fertility of degraded peatlands and improve soybean productivity while supporting the sustainable management and rehabilitation of these ecosystems.